Spontaneous Rupture of the Bicornuate Uterus During 12th Week of Pregnancy - Özçakır, Tayfun; Göker Tamay, Aslı; Buğday, Sultan; Başyurt, Ulaş (Gynecology Obstetrics & Reproductive Medicine, 2011)
To report a case of spontaneous rupture of right horn of the bicornuate uterus, at 12th week of gestation. The presented case was diagnosed and treated at Celal Bayar University Faculty of Medicine Department of Obstetrics and Gynecology. A multiparous patient at 12 weeks of pregnancy, aged 34 presented with acute abdomen and hypovolaemic shock. Upon laparatomy rupture of the right horn of a uterus bicornis was diagnosed. The fetus and placenta were found in the abdominal cavity. Spontaneous rupture of the pregnant uterus generally occurs in congenitally malformed uteri like unicornuate or bicornuate uterus with or without rudimentary communicating-noncommunicating horn. It can be life threatening and should be diagnosed and treated immediately.